Participatory Communication Model for Strengthening Partnership Relations between PT Sukses Mantap Sejahtera and Sugarcane Farmers in Dompu Regency - Muhammad Iqbal; Hari Akbar Sugiantoro (Jogjakarta Communication Conference (JCC), 2026)
Agribusiness partnerships between companies and farmers often face communication challenges that may affect the sustainability of the partnership. This study aims to analyze the implementation of participatory communication in the agribusiness partnership between PT Sukses Mantap Sejahtera (PT SMS) and sugarcane farmers in Dompu Regency. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, field observations, and document analysis, and analyzed using thematic analysis with source triangulation. The findings show that participatory communication is reflected in two-way dialogue, transparency of information, relatively equal relationships, and farmers’ involvement in decision-making related to sugarcane business management. These communication practices help build trust, strengthen coordination, and support the sustainability of the partnership. The study also proposes a participatory communication model emphasizing dialogic interaction and information transparency as the foundation of company–farmer relations.